Exploratory study of the effects of country-of-origin (COO) and brand name cues on consumer buyer behaviour. - Chua, Ai Chuin. (2008)
The purpose of this research study is to explore various dimensions of consumer knowledge, i.e. brand and product knowledge as it relates to country of origin andbranding effects.